PENDAMPINGAN PENGAJUAN SPP-IRT UNTUK PENINGKATAN KEAMANAN PANGAN DI UKM KERUPUK SEMARANG - Siqhny, Zulhaq Dahri; Wahjuningsih, Sri Budi; Indudewi, Dian (Jurnal Abdimas Bina Bangsa, 2025)
Tapioca rambak crackers are the flagship product of UD Mekar, a small industry in Semarang. However, up to this point, the product has not yet obtained the SPP-IRT certification, which is essential to ensure food safety and enhance competitiveness. This community service aims to assist UD Mekar in the SPP-IRT application process, from document preparation to socialization and implementation of Good Manufacturing Practices (GMP). The methods employed include training, administrative assistance, and post-certification monitoring. The results of this activity indicate an increased understanding of food safety among workers and improvements in production facilities. With the acquisition of the SPP-IRT number, UD Mekar can legally market its products, increase consumer trust, and expand its market.